2021
DOI: 10.3390/rs13040672
|View full text |Cite
|
Sign up to set email alerts
|

A Review of GPR Application on Transport Infrastructures: Troubleshooting and Best Practices

Abstract: The non-destructive testing and diagnosis of transport infrastructures is essential because of the need to protect these facilities for mobility, and for economic and social development. The effective and timely assessment of structural health conditions becomes crucial in order to assure the safety of the transportation system and time saver protocols, as well as to reduce excessive repair and maintenance costs. Ground penetrating radar (GPR) is one of the most recommended non-destructive methods for routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(36 citation statements)
references
References 274 publications
(515 reference statements)
0
22
0
2
Order By: Relevance
“…Over the years other methods of assessing pavement conditions have been developed based on roughness, friction, surface deflections. Furthermore, recent developments in fast and accurate non-destructive methods for field conditions, such as ground penetration radar (GPR), can be used for assessing such conditions [13,14].…”
Section: Pavement Condition Assessmentmentioning
confidence: 99%
“…Over the years other methods of assessing pavement conditions have been developed based on roughness, friction, surface deflections. Furthermore, recent developments in fast and accurate non-destructive methods for field conditions, such as ground penetration radar (GPR), can be used for assessing such conditions [13,14].…”
Section: Pavement Condition Assessmentmentioning
confidence: 99%
“…Future research could task itself with additional geostatistical analyses for the structural monitoring of airport runways using integrated non-destructive ground-based technology for surface (e.g., laser scanner [ 9 ]) and subsurface (e.g., Ground Penetrating Radar (GPR), Falling Weight Deflectometer (FWD) [ 14 , 15 , 16 , 76 ]) characterisation of displacements in runways and the improvement of their safety operating conditions.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…Moreover, the power of GPR as a sensing system, covers additional pavement engineering aspects including, among others, density control during pavement compaction monitoring [ 44 ], as well as the assessment of physical properties and pavement subsurface defects [ 45 , 46 ]. Recent reviews of GPR applications in transportation infrastructure can be found in [ 1 , 47 ].…”
Section: Ndt-based Pavement Sensingmentioning
confidence: 99%